2016
DOI: 10.1007/s12671-016-0648-z
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Emotional Exhaustion in the Relationship of Mindfulness with Turnover Intentions and Job Performance

Abstract: AcknowledgementsThe authors wish to thank Lisa Moynihan posthumously for her contributions in conceptualizing an earlier version of this manuscript. AbstractThe role of mindfulness in the workplace has emerged as a legitimate and growing area of organizational scholarship. The present research examined the role of employee emotional exhaustion in mediating the relationship of mindfulness with turnover intentions and task performance. Drawing on theory and empirical research on both organizational behavior and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…With regard to mindfulness training, the question on timing remains: before a crisis, during or after? As discussed, mindfulness is associated with less stress, more job satisfaction, and more engagement (Hyland et al 2015) while also diminishing symptoms of burn-out (Reb et al 2017). Therefore, it can be particularly interesting to use mindfulness as prevention so that attention increases, communication processes improve, and employees can work in a healthy and productive manner.…”
Section: Use Mindfulness As a Preventive Measurementioning
confidence: 99%
See 2 more Smart Citations
“…With regard to mindfulness training, the question on timing remains: before a crisis, during or after? As discussed, mindfulness is associated with less stress, more job satisfaction, and more engagement (Hyland et al 2015) while also diminishing symptoms of burn-out (Reb et al 2017). Therefore, it can be particularly interesting to use mindfulness as prevention so that attention increases, communication processes improve, and employees can work in a healthy and productive manner.…”
Section: Use Mindfulness As a Preventive Measurementioning
confidence: 99%
“…The expectation that employees can better cope with stress, focus better, are more creative, and will possibly even help their coworkers more, motivates different organizations to provide mindfulness training (Carter, Tobias, and Spiegelhalter 2016). In this context, mindfulness is often seen as an anti-burnout remedy, especially because of its association with less emotional exhaustion (Reb et al 2017), which is a core element of burnout. Through this association with lower emotional exhaustion, mindfulness has been related to better performance and less intention to quit (Reb et al 2017;Dane and Brummel 2014).…”
Section: Mindfulness In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, mindfulness has been linked to salutary effects via affective mechanisms, including high positive affect or low negative affect (Erisman & Roemer, 2010;Geschwind, Peeters, Drukker & Van Os, 2011), emotion regulation (Coffey & Hartman, 2008;Hill & Updegraff, 2012;Hülsheger et al, 2013;Prakash & Hussain, 2015), reduced emotional reactivity (Hill & Updegraff, 2012), and lower emotional exhaustion (Reb, Narayanan., Chaturvedi, & Ekkirala, 2016). The cognitive factors highlighted as functions of mindfulness include problem solving (Feldman, Hayes, Kumar, Greeson, & Laurenceau, 2007), cognitive performance (Jensen, Vangkilde, Frokjaer & Hasselbalch, 2012;Jha, Stanley, Kiyonaga, Wong, & Gelfand, 2010;Van Vugt & Jha, 2011), and a positive change in cognitive processing (Bieling et al, 2012;Coffey & Hartman, 2008;Erisman & Roemer, 2010).…”
Section: Problem Solving Confidence and Affect As Mechanisms Linkinmentioning
confidence: 99%
“…Previous studies have demonstrated that employee exhaustion has an impact on work outcomes and employee turnover, which means employees resigning or changing their employers [10,11].…”
Section: Work Outcomes: Job Satisfaction and Turnover Intentionmentioning
confidence: 99%